Teaching small ensemble chamber playing in the large ensemble rehearsal - Selander, Brian (My University, 2025)
The lessons demonstrated in this report are focused on teaching small ensemble playing during the large group rehearsal setting. Playing in a small ensemble requires a different level of playing compared to playing in a larger ensemble. In many ways, it creates a better musician because of the attention to detail needed when only one player is assigned per part. The improvement in musicianship within the smaller ensembles can improve the musicianship when placed back in the larger ensembles. Many schools in our region have well-established small ensemble programs within their band programs. This was something I had yet to develop when I started this project. My outcome for this project was to help establish our small ensemble program by equipping our students with the skills needed to do this on their own next year, without having to go as extensively into the larger group demonstrations as we did with this project. My hope is to build confidence and leadership within my older students and have them pass down what they learned through this project to develop a successful and self-sustaining small ensemble program for years to come. We started by playing through each of the four parts of three different quartets in unison. I then split the band into thirds and assigned each a different quartet. Within each quartet, I assigned each student one of the four parts from their assigned quartet. They played through each part together in their small group, and eventually were able to play as a single player on each of the four parts. Throughout this process, I was teaching them the skills needed to play within a smaller group, and eventually, down to a quartet. Over the course of my master’s program at Kansas State University, I have developed and honed many areas of my music teaching. For starters, I developed my skills and understanding of research. While I spent time in my undergraduate studies developing skills in research, it was nothing compared to what I learned over the course of my time at KSU. I feel more confident in searching for and finding materials for not only the courses I took, but also as an educator looking for ways to improve my craft. I also feel the courses I have taken have provided me with more confidence as a teacher. I feel a strength of mine as a teacher/educator has been my presence in front of my students. I have no problem getting in front of my students/ensembles. However, I feel I am providing better feedback for my students, have enhanced my conducting and rehearsing, and am helping develop musicians within a music program and not just “teaching band,” all because of the things I have learned at KSU. I know I still have not learned everything I can, but I know that going through my graduate studies has given me the passion to want to continue getting better, even as I finish up the work for my master's degree.
Keywords: Small ensemble; Chamber ensemble; Group rehearsal; Band